Polish Independent Press Review, no. 2 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). Interview with an Estonian / by Anna PomianA Polish independent publication has printed an interview with an Estonian, who gives his views on last year's demonstrations in the Baltic states and on Estonia's problems and hopes. This is the first extensive report on Estonia in the independent press. Central Europe: Exposing the Myth / by Anna PomianThe notion of Central Europe both as a political and as a cultural entity has been the subject of numerous articles and reviews in the Polish independent press. Recent voices in the debate have criticized the concept and highlighted those aspects that mistake myth for reality. Polish Historians in Jerusalem / by Anna PomianThe Polish independent press has commented on the recent conference on the history and culture of Polish Jews that was held In Jerusalem. The Garbage Can People, or the New Poor in PolandA recent article in the Polish independent press has documented a new social phenomenon: the emergence of a class of people reduced by economic hardship to living off what they can find in municipal garbage cans. Profiles of Major Independent Polish Publications: "Robotnik - Pismo Członków MRK 'S'" / by Michał Kołodziej"Robotnik - Pismo Członków MRK 'S'" is produced every two weeks in Warsaw by the Interfactory Workers' Committee of Solidarity.